ASSESSING THE IMPACT OF ORGANIZATIONAL CULTURE ON EMPLOYEE JOB SATISFACTION AND ENGAGEMENT AT THONG NHAT HOSPITAL - Thị Hoài, Cao; Thành Toàn, Võ; Chí Hoàng, Cảnh; Kiệm, Đinh; Thị Thanh Quang, Nguyễn; Thị Kim Cương, Lê; Văn Tài, Nguyễn; Đình Thanh, Lê (Journal of Health and Aging, 2025)
Employee job satisfaction and organizational commitment are key factors that determine the effectiveness, stability, and professional development of hospitals in general and public hospitals in particular. This study aims to explore and measure the factors affecting job satisfaction and employee engagement in the healthcare sector from the perspective of organizational culture. Research data was collected from 499 healthcare workers currently employed at Thong Nhat Hospital. Among them, 324 were female (64.9%) and 175 were male (35.1%). The VIF analysis results show that the observed variables had a maximum value of 8.010 and a minimum of 0.713. The test for multicollinearity violations revealed 12 direct impact relationships indicating employee job satisfaction. Of the 11 established factors, only 5 relationships corresponding to 5 factors showed statistical significance at the 5% level: reward and recognition (β = 0.217, p < 0.0001), teamwork (β = 0.200, p < 0.0001), fair compensation (β = 0.157, p < 0.0001), integrity promotion (β = 0.165, p = 0.002), and training and advancement (β = 0.137, p = 0.004). Bootstrapping results showed that 3 moderating variables were not statistically significant, as their p-values were greater than 0.05. There are five factors that positively influence job satisfaction and employee commitment in healthcare, ranked from highest to lowest impact: reward and recognition, teamwork, fair compensation, integrity promotion, and training and advancement.